Towards Better Scrum Learning Using Learning Styles - Scott, Ezequiel (2016)
The meshing hypothesis claims that when both teaching and learning styles are aligned, the students’ learning experience is enhanced. However, the literature fails to evidence support for the meshing hypothesis in the context of software engineering education and scrum learning. For this reason, our work aims to validate the use of strategies for teaching Scrum that fit students’ learning styles according to the Felder-Silverman model.